Environmental Responsibility, Innovation, and Firm Value: A Study of Environmentally Sensitive Industries - Wijayanti, Rita; Lintang Kurniawati; Arinda Herliana; Nadilla Nur Azizah (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2026)
This study aims to analyze the effect of corporate environmental responsibility on firm value, with corporate innovation as a mediating variable, in environmentally sensitive industries in Indonesia. The study uses a sample of 205 companies listed on the Indonesia Stock Exchange during the 2021–2023 period, covering the mining, energy, chemical, and pulp and paper sectors, which are characterized by high environmental risk and strong regulatory pressure. Corporate environmental responsibility is measured using a multidimensional index that includes legal awareness, social evaluation, environmentally friendly production, low-carbon technology, and green management. The results show that corporate environmental responsibility has a positive and significant effect on firm value. In addition, corporate innovation is found to partially mediate this relationship, indicating its role as a mechanism that transforms environmental commitment into long-term economic value. These findings conclude that the integration of environmental responsibility and innovation is a key strategy for enhancing competitiveness and creating sustainable firm value.